The Relationship between Corporate Governance Scored by Thai institute of Directors and Corporate Performance among Thai Listed Companies - Kaewhanam, Kangsadan; Sutthachai, Siriluck; Likitwongkajon, Napaporn (WMS Journal of Management, 2017)
The study aims to investigate the relationship between corporate governance scored by Thai institute of directors (IOD) in 2014 and corporate performance among Thai listed companies. The return on assets ratio (ROA) is used to measure the corporate performance. The samples of this study are 403 Thai listed companies within June 31, 2013. The research used the multiple regressions analysis to investigate the relationship between corporate governance and corporate performance. The results revealed that ROA has positive relationship to corporate governance scored by Thai IOD.